Studi Grounded Theory: Sikap Guru Mengenai Intervensi Aktivitas Fisik dan Diet pada Siswa Obesitas di Sekolah Dasar - Ango, Kezia Aprillia; Ratag, Gustaaf A. E.; Ottay, Ronald I. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2016)
Childhood obesity is recognized as a serious public health problem because of its strong association with obesity during adulthood and other health consequences. The prevalence of overweight and obesity in children worldwide increased from 4.2% in 1990 to 6.7% in 2010 and is estimated to reach 9.1% in 2020. In 2013, the prevalence of obesity in children aged 5-12 in Indonesia is at 8.8%. A study in 2013 showed prevalence of obesity in elementary school children in Manado respectively 32% in boys and 17.6% in girls. Teachers as parents in school have an important role in obesity intervention. This study aimed to discover the attitude of teachers concerning physical activity and dietary intervention in obese children. The study was conducted in three elementary schools in Tuminting District. The results of the study showed that teachers' attitudes toward physical activity and dietary interventions are influenced by teachers' knowledge (cognitive) about obesity and teachers' emotional feeling (affective) towards obese students. Both cognitive and affective aspects have a significant role in raising the teachers' tendency to act (conative) in the implementation of obesity intervention. Obesity interventions that can be done at school were giving advices, suggestions and a weekly physical education. Teachers need parents and primary health centers’ support for the implementation of effective obesity intervention. A cooperation among schools, health centers and local education offices is needed for a successful accomplishment.